Global Perspectives on Freedom of Expression in Environmental Governance: Legal Implications and Challenges - Fatimah, Siti; Wiwoho, Jamal; Isharyanto, Isharyanto (Jambe Law Journal, 2024)
This paper explores the relationship among freedom of expression and earth-friendly governance in a global context, highlighting how the former serves as a fundamental enabler of transparency, public participation, and access to data—principles that are vital to effective earth-friendly governance. Although international legal instruments, such as the Rio Declaration and the International Covenant on Civil and Political Rights, give a framework for upholding free speech, the extent to that this right is realized in the realm of earth-friendly advocacy remains inconsistent across different regions. This research highlights challenges faced by earth-friendly activists, including political and economic pressures, suppression, and legal constraints. By analyzing case studies by Indonesia, Norway, and Brazil, this paper underscores the paradox of freedom of expression that is sometimes perceived as a threat to political stability. The findings advocate for enhanced global cooperation to protect freedom of expression inside earth-friendly law, supporting sustainable enhancement and earth-friendly justice. This paper contributes to a deeper understanding of the legal frameworks necessary to uphold freedom of expression as foundational in promoting global earth-friendly democracy.